Eine Alternative zu der Begriffsbildung "Gott als die alles bestimmende Wirklichkeit" - Knauer, Peter (Zeitschrift für katholische Theologie, 2002)
According to the Christian message, all talk of God must take in account, that God is "incomprehensible". God is to be defined as "whithout whom nothing is". Only in the sense of this sentence, which is based on a unilateral relation of the world towards God, can the affirmation that God "is the all determining reality" be accepted. We only speak really of God acknowledging our being created. The world is explained not by God but by its being created. Thus there is no common concept of being, diffusely overlapping God and the world. The analogy of the world towards God is unilaterally directed. We cannot deduce from God new insights about the world.